ANALISIS DETERMINAN VOLATILITAS NILAI KURS RUPIAH DI INDONESIA TAHUN 2010-2022 - Insulinde Yuliyati; Ayus Ahmad Yusuf; Abdul Aziz (UIN Siber Syekh Nurjati Cirebon, 2023)
The purpose of this research is to analyze the determinants of the volatility of the rupiah exchange rate in Indonesia in 2010-2022. Rising and falling currencies on the money market indicate volatility that occurs in the currency of one country to another. When currency values experience extreme volatility, the economy will experience macro and micro instability. In this study, there are four macroeconomic variables that are thought to influence the Rupiah exchange rate as a dependent variable, including international trade (independent variable I), investment (independent variable II) and foreign exchange reserves (intermediate variable). The location of the research was carried out in the territory of the Republic of Indonesia, this selection was due to the research analyzing the Rupiah exchange rate so that it was relevant as a research location. The research object is the Rupiah Exchange Rate. The data collection technique as a data source uses secondary data obtained through the Central Bureau of Statistics and Bank Indonesia. The data analysis technique in this study is to use path analysis, which is a diagram that connects independent variables, intermediate variables and dependent variables. Relationship patterns are shown. by using arrows, where a single arrow shows a causal relationship between variables. The results of the study used a) the classical assumption test, consisting of, among other things, the normality test, multicollinearity test and autocorrelation test and heteroscedasticity test. (b) validity test. Based on the results of the discussion of research on Determinant Analysis of Rupiah Exchange Rate Volatility in Indonesia in 2010-2022 is an international trade variable has a positive and significant effect on the rupiah exchange rate, export and import variables have a positive effect on economic growth. Investment variables have a positive and significant effect on the rupiah exchange rate, while foreign exchange reserves have an indirect effect on the rupiah exchange rate.Keywords: Rupiah Exchange Rate, International Trade, Investment, Foreign Exchange Reserves.